The Development of Interactive Media Tour in Cell to Improve Cognitive Skills of High School Students - Nisa', Muallimatun (FMIPA UNNES, 2022)
The purpose of this study is to find out the feasibility and effectiveness of Tour in Cell interactive media to improve the cognitive skills of high school/MA students. This research uses Research and Development methods consisting of needs analysis, data collection, product design, media validation and design by experts, design revisions, small-scale product trials, product revisions, and wide-scale product trials. Product design in the form of Interactive Media Tour in Cell with material validity of 4.33 including category is very feasible 86.67% and media display validity of 4.13 including category is very feasible with a percentage of 82.72%. At the wide-scale trial stage, the improvement in student learning outcomes with the N-gain test resulted in an average N-gain score of 0.59 with moderate criteria. Based on the results of the study can be concluded that the media Tour in Cell developed is worth using.